Identification and quantification of phenolic compounds in mangifera indica waterlily kernel and their free radical scavenging activity - Al-Shwyeh, Hussah Abdullah; Sabo Muhammed, Abdulkarim; Abdullah, Rasedee; Mirghani, Mohamed Elwathig Saeed (Journal of Advanced Agricultural Technologies, 2015)
The aim of this study was to determine phenolic compounds and antioxidant capacity of extract prepared from Mangifera indica waterlily kernel. Acidified methanolic extract prepared from M. indica waterlily kernel was analyzed. The total phenolic content was determined by the Folin_Ciocalteu method. Antioxidant activity was measured by the 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging activity and ferric-reducing antioxidant power (FRAP) assays. Characterization of phenolic compounds was conducted using HPLCDAD and TSQ-ESIMS and Peak identities were confirmed by comparing their retention times, UV_vis absorption spectra, and mass spectra with authentic standards. The total phenolic content of M. indica waterlily kernel was 8.6 mg GAE/g DW. The seeds extract showed a strong potency of antioxidant activity as confirmed by the DPPH radical scavenging activity, and FRAP assays. Epigallocatechin (EGC), chlorogenic acid, apiginin, and epicatechin were the major compounds among the 12 phenolics that have been identified and quantified in M. indica waterlily kernel with 21.8, 13.7, 3.2 and 2.7 mg/g M. indica waterlily kernel, respectively. The 12 phenolic compounds identified in M. indica waterlily kernel using HPLCDAD and TSQ-ESI-MS had high antioxidant activity and should be considered as a prospective antioxidant.